Homozygous mutation in the NPHP3 gene causing foetal nephronophthisis. Issue 10 (October 2017) - Abdullah, Uzma; Farooq, Muhammad; Fatima, Ambrin; Tauseef, Wasima; Sarwar, Yasra; Nuri, Mmh; Tommerup, Niels; Baig, Shahid M.
Abstract: We present a case of a foetal sonographic finding of hyper‐echogenic kidneys, which led to a strategic series of genetic tests and identified a homozygous mutation (c.424C > T, p. R142*) in the NPHP3 gene. Our study provides a rare presentation of NPHP3‐related ciliopathy and adds to the mutation spectrum of the gene, being the first one from Pakistani population. With a thorough literature review, it also advocates for molecular assessment of ciliopathies to improve risk estimate for future pregnancies, and identify predisposed asymptomatic carriers.